Zika virus disrupts gene expression in human myoblasts and myotubes: Relationship with susceptibility to infection. - Ingo Riederer; Daniella Arêas Mendes-; Guilherme Cordenonsi da Fonseca; Mariela Natacha González; Otavio Brustolini; Cássia Rocha; Guilherme Loss; Joseane Biso de Carvalho; Mariane Talon Menezes; Lidiane Menezes Souza Raphael; Alexandra Gerber; Myrna Cristina Bonaldo; et al. (Public Library of Science (PLoS), 2022)
The tropism of Zika virus (ZIKV) has been described in the nervous system, blood, placenta, thymus, and skeletal muscle. We investigated the mechanisms of skeletal muscle susceptibility to ZIKV using an in vitro model of human skeletal muscle myogenesis, in which myoblasts differentiate into myotubes. Myoblasts were permissive to ZIKV infection, generating productive viral particles, while myotubes controlled ZIKV replication. To investigate the underlying mechanisms, we used gene expression profiling. First, we assessed gene changes in myotubes compared with myoblasts in the model without infection. As expected, we observed an increase in genes and pathways related to the contractile muscle system in the myotubes, a reduction in processes linked to proliferation, migration and cytokine production, among others, confirming the myogenic capacity of our system in vitro. A comparison between non-infected and infected myoblasts revealed more than 500 differentially expressed genes (DEGs). In contrast, infected myotubes showed almost 2,000 DEGs, among which we detected genes and pathways highly or exclusively expressed in myotubes, including those related to antiviral and innate immune responses. Such gene modulation could explain our findings showing that ZIKV also invades myotubes but does not replicate in these differentiated cells. In conclusion, we showed that ZIKV largely (but differentially) disrupts gene expression in human myoblasts and myotubes. Identifying genes involved in myotube resistance can shed light on potential antiviral mechanisms against ZIKV infection.